The Potential of Activated Carbon from Durian (Durio Zibenthius) Peel Waste As An Adsorbent Of Oil Spill - Yulyani Nur Azizah; Nur Azizah Dwi Ningrum; Nurhasni (Jurnal Riset Sains dan Kimia Terapan, 2025)
Oil exploration activities, such as ship loading and unloading, can lead to oil spills at sea, as can oil spills and tanker collisions. An affordable method for dealing with these spills is adsorption using activated carbon derived from bio-waste, such as durian peel. This study aims to evaluate the adsorption efficiency of durian peel-activated carbon on oil spills. The carbonization of durian peel was carried out at 300 °C and activated with KOH at 5, 20, 35, and 50% (w/v). Durian peel activated carbon with 35% KOH showed the best results for moisture content (5.442%), ash content (4.457%), bound carbon content (72.050%), and iodine adsorption (896.033 mg/g), according to SNI 06-3730-1995. FTIR measurements revealed that KOH activation did not induce significant changes in the wavenumbers of functional groups, but did increase the pore diameter, as confirmed by SEM. Its adsorption efficiency with a batch system on crude oil in simulated and real seawater reached 90.182% and 90.091%, respectively. These results suggest that activated carbon from durian peel has excellent potential as an oil adsorbent. This would increase its utility value and reduce the accumulation of biomass waste.